L’Antropologia nella Primary Health Care. Costruire gli Ospedali di Comunità, tra cure intermedie e nuove forme di cooperazione - Belluto, Martina; Consoloni, Martina (Antropologia Pubblica, 2024)
Chronic diseases, population ageing, and recent social changes have highlighted the urge of strengthening intermediate care. This concept refers to a wide range of services which have the aim of addressing the health needs of people who have been discharged from the hospital to home in order to better coordinate longitudinal and community-oriented care. Given the complex nature of the health needs which emerge in this scenario, health facilities must provide different disciplines, skills and tools based on the contexts and the relations that substantiate care practices. In perspective, medical anthropology/ical knowledge can play a decisive role. However, such input requires a transformation of university education, including humanistic and anthropological curricula, by addressing them primarily to fieldwork and engaged research in communities, which is still weakly realized in Italy. This article focuses on an action research project that we carried out, as Ph.D. students and anthropologists, within an international cooperation and health policies project developed between the Emilia-Romagna Region and Brazil, in 2019. The text discusses the contributions made by ethnographic, applied and distinctly interdisciplinary Ph.D. research, which can constitute a resource for promoting forms of participatory and community planning of health services.